THE DETECTION OF A VIRAL INTERFERING SUBSTANCE IN THE SHOPE PAPILLOMA AND THE Vx7 AND Vx2 CARCINOMAS - Langston, Deborah Pavan (The Rockefeller University Press, 1967)
In vivo assay of Shope papilloma protein extract and in vitro assay of extracts from Shope papilloma, Vx7 and Vx2 carcinomas showed strong interferon-like activity in the papilloma and moderate activity in the carcinomas. The interpretation is that the presence of viral nucleic acid in all three tumors stimulated the production of this substance even though fluorescent antibody studies reveal the protein coat only in the papilloma and Vx7.